The Impact of an Explicit Writing Intervention on EFL Students’ Short Story Writing - Tsiriotakis, Ioanna K.; Grünke, Matthias; Spantidakis, Ioannis; Vassilaki, Eleni; Stavrou, Nektarios A. M. (Frontiers in Education, 2020)
Educational research has shown that a high ability to use effective strategies, a broad fount of metacognitive knowledge, and fostering of adaptive beliefs about writing lead to better text production performance. Explicit instruction enhances development in each of these areas. The aim of the present study was to examine the effects of a writing intervention program (based on the strategies “POW” and “WWW”) on the quality and length of stories composed by Greek grade 5 and 6 English Foreign Language (EFL) learners. The study was conducted with 177 participants from two Greek elementary schools, who were identified as below average, average, and above average writers, and who were assigned to one of two groups: the experimental group was provided with explicit instruction on narrative writing, the control group received no direct teaching and followed the guidelines outlined by a traditional writing program. It was postulated that explicit instruction would have a positive impact on students’ writing skills. Data analysis yielded statistically significant differences between experimental and control conditions. The students in the experimental group outperformed the ones in the control group in all writing assessments (pertaining to text quality and length). They also revealed a significant improvement in their writing quality and length, whereas no meaningful changes appeared in the control group. In addition, the improvement of writing quality was obvious for the below average, as well as, for the average and the above average students, supporting the notion that there was an improvement irrespective of the students’ level. These results speak to the practical effectiveness of explicit writing instruction to improve the story composition skills in grade 5 and 6 EFL learners. It is postulated and may be the subject of future research that the positive impact on students’ L2 composing skills will be transferrable to their L1. Conclusions and pedagogical implications of the findings are discussed.